Kondisi Substrat Dasar Perairan Cagar Alam Pulau Sempu, Kabupaten Malang - Oktiyas Muzaky Luthfi; Firly Yulianto; Sanydo Pandapotan Caesar Pangaribuan; Dimas Bagus Dwi Putranto; Dimas Syarif Alim; Respati Dwi Sasmitha (Fakultas Kelautan dan Perikanan Universitas Udayana, 2019)
The aim this study was to determine the condition of bottom substrate base of Sempu Island Nature Reserve of Malang that was very important to know the coral reef composition to support living creatures in this area. The research was conducted on December 8-9, 2017, the substrates data was taken by using Point Intercept Transect (PIT) for 100 m along of coast of Sempu Island (Reef Check Indonesia), the transect was divided into four parts 20 meters each segment and 5 m blank between segments. The data was taken into three stations, they were Teluk Semut 1 , Teluk Semut 2, and Watu Meja. The results of this study indicate that the basic substrate of waters at Sempu Island Nature Reserve is divided into two: living (HC = Hard Coral, SC = Soft Coral, NIA = Nutrien Indicator Algae, SP = Sponge and OT = Other) and non-living (RKC = Ricently Killed Coral, RC = Rock, RB = Rubble, SD = Sand and SI = Silt). Teluk Semut Station 1 was dominated by the rubble (39%), Teluk Semut 2 station and Watu Meja were dominated by hard coral (53%). In conclusion, from three monitored stations showed that the life coral percentage in Sempu Island water was significane changed during last one year where in Teluk Semut 1 the coral coverage decreased to 21.75%, while in Teluk Semut 2 and Watu Meja was increased up to 42.38% and 25.5% respectively. The natural and non-natural factors may have influenced the changed of substrate cover in Sempu Island water during this last year.